Terapi Wudhu dan Hyigiene terhadap Gangguan Tidur Anak Usia Sekolah - Mariyana, Rina; Oktorina, Rola; Pratama, Andiesta (Universitas Fort De Kock Bukittinggi, 2020)
Background: Sleep disturbance is a problem that often arises in the population of school-age children where every year around 20% to 50% of sleep disorders and about 17% experience serious sleep disorders caused by various factors. Wudhu therapy and sleepy hygienic therapy is one of the therapies that can be used to overcome sleep disorders. The purpose of this research is to find out the influence of wudhu therapy and sleepy hygiene therapy on sleep disorders in school-age children. Method: The research method used is Quasi Experiment Design with Pre Test and Post Test Two Group Design designs. in the application with design interpretation - posttest. The sampling technique was taken by purposive sampling method with a sample of 20 respondents. Data analysis used in this study is the analysis of univariated and bivariated with using T test. Results: Average sleep disturbance of respondents before (pretest) wudhu therapy was 55.50 and after (posttest) wudhu therapy was given 30.10 with a P-value of 0.001 and obtained an average sleep disturbance before respondents (Pretest) performed sleepy hygiene therapy was 56.80 and after (posttest) given sleepy hygiene therapy was 42.60 with a P-value of 0.002. The results showed ablution therapy is more effective than sleepy hygiene therapy. Conclusion: There is an influence of wudhu therapy and sleepy hygiene therapy on sleep disorders in school-age children. Suggestions in this study if a child has a sleep disorder can perform wudhu therapy and sleepy therapy hygiene so sleep becomes comfortable.